Análisis económico para la implementación de las normas globalgap en la finca bella María en el sitio San Antonio - Moran Gamez, María Fernanda (2017)
The banana sector in Ecuador generates more than 2 million jobs, occupies the second place of income in the country's economy, 30% of the world's banana supply comes from our country. The provinces with the highest production of bananas are Los Ríos, Guayas and El Oro; The banana varieties that the country exports are Cavendish, orito and red banana. The production costs for one hectare of banana in 2015 was USD 8,786.85 where the items to be taken into account are cultural work, phytosanitary control, harvesting and fertilization. The export of Ecuadorian bananas in the first quarter of 2007 is 89,008,343 boxes of bananas with an income of 849.91 thousand USD. FOB.At present, international trade in the agro-industry has been interested in welfare, social and environmental in the food safety process, and therefore producers are required to use international standards certifications that comply with this request. The GLOBALGAP norms aims to assure to the consumer fresh foods and that they are produced under the implementation of Good Agricultural Practices, reducing the use of agrochemicals, the risk of the environmental impact and finally it foments the responsible operations in the farm; On the other hand, producers have certain advantages in implementing them, they have a quota to export to markets that require this type of certification, increase their competitive advantages and improve the quality of products, processes and services. But obtaining this certification produces a certain cost since some improvements have to be made to the infrastructure of the baler, in case there are no bathrooms to make them, to buy materials, tools and equipment; With the aim of ensuring the welfare of workers, having a safe product and preserving the environment.This study analyzed the feasibility and benefits of implementing the standard GLOBALGAP, to meet this goal were determined the production costs of the fine "Bella Maria", which details the investment that the owner had to do to obtain certification , The costs of producing a banana box by comparing them with banana production costs of an uncertified farm; A cash flow was made to determine the IRR and the Van, with this being verified if the farm had profit or losses with the investments made during its productive period. Banana production was also analyzed in the period 2014-2016 of the farm to establish the relation of the boxes produced and the annual sales where it was priced that this period of time there was a decrease in the production of banana boxes in 2015 The justification was that there were phytosanitary problems; Finally, the advantages obtained by implementing the GLOBALGAP standards will be described by means of an interview with different banana producers of the San Antonio site in the canton Santa Rosa, obtaining a favorable result.